Analisis Kesalahan Berbahasa Dalam Penulisan Insya’ di Madrasah Tsanawiyah Badridduja - Mu’alim Wijaya; Kholifah (Universitas Yudharta Pasuruan, 2021)
This research is related to the analysis of linguistic errors in writing insya' in class VII(B) Madrasah Tsanawiyah Badridduja. The purpose of this study is to identify the various language errors that occur, the causative factors and solutions that can be done to correct these problems. The research method used is an associative quantitative approach with data collection techniques using written media in the form of written tests, observations and interviews. Then the researcher classified the errors into 4 categories. Based on the results of the research, from the results of the written essay writing test (insya') found 38 errors with 4 categories: in the phonological order 10 errors, the morphological order 6 errors, the syntactic order 13 errors and in the semantic order 9 errors. Based on the data from the recapitulation of the first test before the evaluation, it obtained an average score of 40 with the data from the recapitulation of the second test after the evaluation, obtaining an average value of 71.5. So, this shows that the evaluation activities carried out by researchers on students' language errors went well and showed an increase in the ability of students' maharah kitabah.